Fat and sugar rich dietary pattern is associated with negative metaphorical statement in metabolically healthy overweight and obese men and women - Abdollahi, Morteza; Mckian, Somayeh Sadat Mckian; Jamhidi, Sanaz; Esmaeilinezhad, Zahra; Mohammadipoor, Nazanin; Hashemi, Baran; Mazloomi, Seyed Mohammad (Progress in Nutrition, 2020)
Considering that metaphoric statement indicates individuals’ comprehension of health issues, we aimed to assess whether obese individuals’ metaphorical expression of either self or their own lives is related to their dietary pattern. Two hundred and ten metabolically healthy adult men and women who attended diet clinics in Shiraz participated in this cross-sectional study. A validated 168 food item FFQ was used for dietary assessment. To assess the individual’s metaphorical statement of themselves and their own lives, Osgood semantic differential method was used. Three dietary patterns were extracted using principal component analysis with the orthogonal rotation Varimax with Kaiser Normalization. Mediterranean dietary pattern including leafy vegetables, other non-starchy vegetables, fruits and fruit juices, low fat dairy, olive, and olive oil; inflammatory dietary pattern including refined grains, high fat dairy, hydrogenated oils, sweets, and ice cream; and snacking dietary pattern including snacks, pickles, carbonated drinks, and sweetened juices. Both Mediterranean pattern and inflammatory pattern had a significant association with body mass index (P= 0.03 and P= 0.01, respectively). Significant association was also found between inflammatory dietary pattern and waist circumference (P= 0.001). A negative association were found between inflammatory and snacking dietary patterns and metaphor of self (P= 0.003 and P= 0.003, respectively) and life (P= 0.03 and P= 0.01, respectively) questionnaire scores. Diet high in starch and sugar as well as hydrogenated fats is associated with negative narration of individuals’ embodied experience about themselves and their own lives.